THE USE OF ANTHROPONIMS IN CHILDREN’S SPEECH - Jumaeva Dilnoza Baxshulloevna; Haziqova Sevil Husniddin qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides an overview of the use of unique, anthropomorphous people in children’s speeches, the fact that anthroponimic access units in children’s speech are one of the most essential tools of the communication process, that they serve to perform connotative, appellant, and emotional tasks in speech, and that the units of access are the anthropomorphic units that are widely used in the speech process and serve to interact task characteristics are revealed. The use of anthropomorphs in children’s speech is illustrated by artifacts, and through anthropomorphists, some aspects of speech are explained in children’s language.